Promotion Media Recommendations on The Acceptance of New Students In Private Educations With The Simple Additive Weighting Method - R. Fanry Siahaan; Liber Simbolon (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Ensuring the existence of private universities (PTS) is the number of new students who enrol in each new academic year. One of the ways that private universities STMIK Pelita Nusantara to attract new student candidates is through promotion. Promotion is a communication activity carried out to introduce something to the public and simultaneously influence the wider community to buy and use the product. The purpose of this study was to determine which promotional media was more effective which had an impact on the number of new student enrollments at the private tertiary education institution STMIK Pelita Nusantara using the SAW method as a measuring instrument. The steps taken are: determining the value of the criteria for each alternative, determining the weight, normalizing the matrix, and normalizing the decision matrix to a scale that is compared to all the alternative ratings. The result of the research is the promotion mix with the alternative Worth of Mouth promotion as the best media with a value of 1.